Milk urea concentration in Holstein and Simmental cows - Darija Bendelja; Zvonimir Prpić; Nataša Mikulec; Zdenko Ivkić; Jasmina Havranek; Neven Antunac (Mljekarstvo)
Determining the urea concentration in milk is a useful indicator of the nutritional protein status of the organism as well as of the ratio between the energy and the protein in ruminant rations, with increasing practical usage. In addition to nutrition, milk urea concentration is influenced by a whole range of factors, for example: breed, stage and number of lactations, body weight, daily production and chemical composition of milk, somatic cell count, season and milking. The objective of this research was to determine the impact of the cow breed (Holstein and Simmental), the number of lactation (1st, 2nd, 3rd, 4th, 5th), milking time (morning-evening) and season (spring-summer and autumn-winter) on milk urea concentration. The following was determined for each breed: daily milk yield, milk fat, protein and lactose content, urea concentration and somatic cell count in milk. Statistical data processing was carried out by applying General Linear Model procedure, SAS system (1999). The cow breed had a significant influence on daily milk yield and log somatic cell count (P<0.001), lactose content in milk (P<0.01), milk fat content and milk urea concentration (P<0.05). The number of lactations significantly influenced daily milk yield (P<0.001), protein content (P<0.001 and P<0.01) and milk urea concentration, but only for Holstein breed (P<0.05). Milking time significantly influenced the fat and protein content (P<0.001) in the milk of Holstein cows, that is, lactose content (P<0.05) and urea concentration (P<0.05) in the milk of Simmental cows. The season significantly influenced the fat and protein content of milk (P<0.001), that is, urea concentration and log somatic cell count (P<0.01). Determining of urea concentration in cow milk should also be systematically conducted in the Republic of Croatia, in order to determine standard physiological values characteristical for a particular cow breed, aiming to determine the balance of energy and protein in rations.